THE IMPLEMENTATION OF ‘BRITISH PARLIAMENTARY DEBATE SYSTEM’ IN LEARNING DISCUSSION TEXT - Siallagan, Meri Kristina (PEOPLE: International Journal of Social Sciences, 2017)
Current curriculum requires that teaching-learning process should be able to stimulate students’ critical thinking. In order to achieve the goal, teachers are expected to find and design a learning method where the students will participate in class discussion. Consequently, teacher initiates a study which attempts to reveal the implementation of British Parliamentary Debate System in learning discussion text for grade XII in SMA Unggul Del. This study design is based on speaking experiment where students in a team will be separated in government (proposition) side and opposition’s side. The researcher is using qualitative data to make sure that British Parliamentary Debate is totally beneficial for the students to enhance their arguments for two perspectives as discussion text mean to be. The result is British Parliamentary Debate is compatible with discussion text as it evaluates matter from different perspectives. Thus, based on the findings, the researcher strongly recommends British Parliamentary Debate to evaluate students’ speaking skills. Furthermore, through this implementation, students are expected to be more critical in building their knowledge and opinions. Further research is expected to broaden the scope not only for senior high scool students.